Kelayakan Investasi dengan Metode Return on Investement (ROI) pada Proyek Pembangunan Perumahan Chrysant Luxury Land Lamongan - Arifah, Wanda Sholihatul; Agustapraja, Hammam Rofiqi; Arif, Samsul (Universitas Batanghari Jambi, 2025)
The growth of the residential property market, particularly in the housing sector is currently experiencing a slowdown. This condition is influenced by economic instability and a decline in consumer purchasing power. Such circumstances pose significant challenges for developers and investors, especially those in the project development phase. Based on this background, this study aims to evaluate the financial feasibility of an investment in the Chrysant Luxury Land Housing Project, which is also expected to serve as a reference for future residential development and planning. The research method employed is Return on Investment (ROI), focusing on the construction of 11 housing units. The data analyzed include revenue details, total expenditure, and the project site plan as the basis for financial calculations and simulations. The analysis results show an ROI value of 8.8%, indicating a positive return. This suggests that the project is financially profitable and feasible to proceed as an investment endeavor.